Population Displacement and Housing Dilemmas Due to Catastrophic Disasters - Levine, Joyce N.; Esnard, Ann-Margaret; Sapat, Alka (Journal of Planning Literature, 2007)
As Hurricane Katrina revealed, coastal communities have become far more vulnerable to tropical storms and the long-term displacement of residents. Yet, because the emergency management model presumes that recovery quickly follows response, governments focus only on short-term, localized displacement. However, long-term and long-distance displacement exposes a gray area between immediate shelter and permanent housing, along with concerns about vulnerability, housing availability, and land development. We begin this article by discussing the transition between response and recovery. We then review literature regarding social vulnerability, displacement, provision of temporary housing, households' return decisions, and disaster-driven land development and housing construction processes. We close with thoughts on future research to increase planners' understanding of the issues involved and to help them craft effective policies.

Institutions and the losses from natural disasters - Raschky, Paul A. (Natural Hazards and Earth System Sciences, 2008)
Abstract. Natural hazards can be seen as a function of a specific natural process and human (economic) activity. Whereby the bulk of literature on natural hazard management has its focus on the natural process, an increasing number of scholars is emphasizing the importance of human activity in this context. Existing literature has identified certain socio-economic factors that determine the impact of natural disasters on society. The purpose of this paper is to highlight the effects of the institutional framework that influences human behavior by setting incentives and to point out the importance of institutional vulnerability. Results from an empirical investigation of large scale natural disasters between 1984 and 2004 show that countries with better institutions experience less victims and lower economic losses from natural disasters. In addition, the results suggest a non-linear relationship between economic development and economic disaster losses. The suggestions in this paper have implications for the discussion on how to deal with the adverse effects of natural hazards and how to develop efficient adaption strategies.
MAG ID: 2144494290

Comparison of Hydrologic Responses at Different Watershed Scales - Mohamoud, Yusuf (2004)
Land surface hydrology controls runoff production and the associated transport of sediments, and a wide variety of anthropogenic organic chemicals, and nutrients from upland landscape areas and hillslopes to streams and other water bodies. Based on interactions between landscape characteristics and precipitation inputs, watersheds respond differently to different climatic inputs (e.g. precipitation and solar radiation). This study compares the hydrologic responses of the MidAtlantic watersheds, and identifies the landscape and climatic descriptors that control those responses. Our approach was to select representative watersheds from the Mid-Atlantic region, group the watersheds by physiographic province and ecoregion, and then collect landscape, climate, and hydrologic response descriptor data for each selected watershed. For example, we extracted extensive landscape descriptor data from soil, land use and land cover, and digital elevation model geographic information system (GIS) databases. After sufficient data was collected, we conducted a variety of studies to determine how different landscape and climatic descriptors influence the hydrologic response of Mid-Atlantic watersheds. This report is comprised of four main parts. Part I describes the selection of the representative study watersheds and the determination of representative physical landscape descriptors for each watershed using geographic information system analysis tools. Part II characterizes the climate and associated hydrologic responses of the study watersheds. To select climate descriptors that are good predictors of hydrologic response, we examined a large number of candidate descriptors. Based on our examination, we selected dryness index and mean monthly rainfall as the best hydrologic response predictors. In Part II, we also present the results of our study hydrologic response comparisons of the study watersheds using a water balance approach. The water balance approach was based on comparisons of precipitation, streamflow, and evapotranspiration at annual, monthly, and daily time scales. These comparisons revealed that elevation and latitudinal position strongly influence hydrologic response. The results also showed that mountainous watersheds of the Appalachian Plateau, Ridge and Valley, and Blue Ridge Physiographic Provinces have more streamflow and less evapotranspiration than watersheds located in the Piedmont Province, and that snowmelt contributes a large portion of streamflow. Part III presents relationships we derived between landscape-climatic descriptors and the hydrologic response descriptors. Flow duration indices (Q1...Q95) were used to represent the hydrologic responses of the study watersheds. In Part III, we also present comparisons of the hydrologic responses of the study watersheds at high flow condition, represented by the Q1 index, medium flow condition represented by the Q50 index, and low flow condition represented by the Q95 index. These comparisons revealed that: the Appalachian Plateau, ridge-dominated Ridge and Valley, and Blue Ridge watersheds have the highest Q1 and Q50 indices; the valley-dominated Ridge and Valley watersheds have the lowest Q50 index, and the Piedmont watersheds have the lowest Q1 index and a relatively high Q95 index. Finally, Part IV discusses some of the implications of the study results for watershed management. We also present applications of the research for hydrologic modeling and watershed assessment.
Keywords: Ouvrage_Collectif_Numéro1

Natural and imposed injustices: the challenges in implementing 'fair' flood risk management policy in England - Johnson, Clare L.; Penning-Rowsell, Edmund C.; Parker, Dennis J. (The Geographical Journal, 2007)
This paper examines the challenges facing English flood risk management (FRM) policy and practice when considering fair decision-making processes and outcomes at a range of spatial scales. It is recognised that flooding is not fair per se : the inherent natural spatial inequality of flood frequency and extent, plus the legacy of differential system interventions, being the cause. But, drawing on the three social justice models – procedural equality, Rawls’ maximin rule and maximum utility – the authors examine the fairness principles currently employed in FRM decision-making. This is achieved, firstly, in relation to the distribution of taxpayer’s money for FRM at the national, regional and local levels and, secondly, for non-structural strategies – most notably those of insurance, flood warnings and awareness raising, land use control, home owner adaptation and emergency management. A case study of the Lower Thames catchment illustrates the challenges facing decision-makers in ‘real life’: how those strategies which appear to be most technically and economically effective fall far short of being fair from either a vulnerability or equality perspective. The paper concludes that if we are to manage flood risk somewhat more fairly then a move in the direction of government funding of nationally consistent non-structural strategies, in conjunction with lower investment decision thresholds for other local-level FRM options, appears to offer a greater contribution to equality and vulnerability-based social justice principles than the status quo.
MAG ID: 1986630856

The macroeconomic consequences of disasters - Noy, Ilan (Journal of Development Economics, 2009)
Natural disasters have a statistically observable adverse impact on the macro-economy in the short-run and costlier events lead to more pronounced slowdowns in production. Yet, interestingly, developing countries, and smaller economies, face much larger output declines following a disaster of similar relative magnitude than do developed countries or bigger economies. A close study of the determinants of these adverse macroeconomic output costs reveals several interesting patterns. Countries with a higher literacy rate, better institutions, higher per capita income, higher degree of openness to trade, and higher levels of government spending are better able to withstand the initial disaster shock and prevent further spillovers into the macro-economy. These all suggest an increased ability to mobilize resources for reconstruction. Financial conditions also seem to be of importance; countries with more foreign exchange reserves, and higher levels of domestic credit, but with less-open capital accounts appear more robust and better able to endure natural disasters, with less adverse spillover into domestic production.
MAG ID: 1965840936

Mapping Urban Risk: Flood Hazards, Race, & Environmental Justice In New York" - Maantay, Juliana A.; Maroko, Andrew R. (Applied Geography, 2009)
Abstract This paper demonstrates the importance of disaggregating population data aggregated by census tracts or other units, for more realistic population distribution/location. A newly developed mapping method, the Cadastral-based Expert Dasymetric System (CEDS), calculates population in hyper-heterogeneous urban areas better than traditional mapping techniques. A case study estimating population potentially impacted by flood hazard in New York City compares the impacted population determined by CEDS with that derived by centroid-containment method and filtered areal-weighting interpolation. Compared to CEDS, 37% and 72% fewer people are estimated to be at risk from floods city-wide, using conventional areal weighting of census data, and centroid-containment selection, respectively. Undercounting of impacted population could have serious implications for emergency management and disaster planning. Ethnic/racial populations are also spatially disaggregated to determine any environmental justice impacts with flood risk. Minorities are disproportionately undercounted using traditional methods. Underestimating more vulnerable sub-populations impairs preparedness and relief efforts.
MAG ID: 1965301779